Feto-maternal outcome in early-term, full-term, late-term and post-term pregnancies at a tertiary centre in India - Agrawal, Nisha; Modi, Jyoti Nath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The risk of perinatal complications does not remain consistent over the 5-week period between 37-42 weeks taken as ‘Term pregnancy’. The American College of Obstetrics and Gynecology (ACOG) has further classified this period into Early term (ET) (37-38+6 weeks), Full term (FT) (39-40+6 weeks) and Late term (LT) (41-41+6 weeks), besides Post term (PT) (>42 weeks). The present study evaluates the feto-maternal outcomes in deliveries at various term gestations as per this new classification in Indian settings. Methods: This is a retrospective record-based study of women delivering at a tertiary care medical college hospital in central India between 1st January 2014 and 31st December 2017. Low risk spontaneous deliveries with confirmed gestational age of 37 completed weeks or more, with single fetus in vertex presentation were analyzed. Those with incomplete records or complications such as preeclampsia, gestational diabetes mellitus, heart disease, antepartum hemorrhage, etc. were excluded. Results: Out of 1498 case-records that satisfied the criteria, 722 (48.2%) were ET; 690 (46.1%) were FT; 76 (5%) were LT and 10 (0.7%) were PT. A significantly higher proportion of women who delivered post-term were from rural area, lacked institutional antenatal care visits and had lesser formal education. Caesarean Section (CS) rate was significantly higher in the PT group (60%) compared to the other groups ET (40.9%), FT (39.7%), and LT (39.5%). The PT group also had a significantly higher rate of Meconium-Stained Liquor (MSL), APGAR<7 and still births. The maternal and fetal parameters were not significantly different between the ET, FT and LT groups except birth weight (BW). Conclusions: The post-term pregnancies have a higher risk of MSL, still birth, APGAR <7, and delivery by CS. Women with lesser education, those from rural areas and who have not received institutional antenatal care are more likely to report in late and PT. Larger studies in our settings are needed to evaluate and compare the maternal and fetal outcomes in pregnancies delivering at ET, FT, LT and PT gestations.